Nonlinear Analysis Of Asymmetric Rc Building Under Repeated Ground Motions - Osman, Ahmed Abdallah Mohammed (2011)

(untitled)
This study deals with the nonlinear response of an asymmetrical reinforced concrete building under single and repeated earthquake ground motions. Two main categories of ground motions, namely near-fault and far-fault, have been taken into consideration in this study. A full scale of a four-storey reinforced concrete building is experimentally tested by European Laboratory for Structural Assessment (ELSA) in Ispra, and the results from experimental test is compared with the numerical results conducted by this study. Then, many ground motions records, recorded in (stiff soil), are assigned to the building followed by the repeated ground motions. The repetition cases are created by considering two cases, the first case considers main-shock and after-shock while the second case considers fore-shock, main-shock and after-shock. The results obtained by far-fault are compared with near-fault results, also the repetition cases are compared with the single ground motion case in terms of top floor displacement, lateral displacement, rotation and interstorey drift ratio. The main finding of this study is from a qualitative point of view the sequence of ground motions lead to higher responds compared with the single case, consequently more damage will occur under repeated cases which should be considered when evaluating structures performance under seismic loads